Persepsi Mahasiswa terhadap Urgensi Perlindungan Hukum Ikan Napoleon Sebagai Spesies Laut Langka dalam Kebijakan Perikanan - Sarndika Sarndika; Wa Ode Siti Safiyah; Fitriyana Fitriyana (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This study aims to analyze the perceptions of students from various majors regarding the urgency of legal protection for the Napoleon wrasse (Cheilinus undulatus), a rare and endangered marine species that plays a crucial role in maintaining the balance of coral reef ecosystems. This fish faces serious pressure due to overexploitation and illegal trade, thus requiring special attention from a legal and conservation perspective. This study used a qualitative descriptive approach with purposive sampling technique, involving students from marine, fisheries, environmental, and legal departments. Primary data were collected through a questionnaire designed to elicit respondents' insights, level of understanding, and recommendations regarding the protection of this species. The data obtained were then analyzed using thematic analysis to identify patterns of perception and key ideas. The results showed that the majority of students considered legal protection for the Napoleon wrasse to be very urgent. They advocated for strengthening regulations, stricter law enforcement, increased surveillance in water areas, education for coastal communities, development of conservation and cultivation programs, and strengthening international cooperation. The implications of this study emphasize the importance of a comprehensive and collaborative protection strategy to support the sustainability of marine resources.